The Effect of Nurse Caring Training Based on Jean Watson's Theory in Medical Ward - Oktiva, Yayuk Dwi; Rahayu, Umi Budi; Rahayuningsih, Faizah Betty (Sekolah Tinggi Ilmu Kesehatan Kendal, 2023)
Nurses' caring behavior is part of the quality of care indicators in hospitals. Caring is a complex part of nursing and an important value in the life of professional nurses. This study aims to determine the effect of nurse caring training to improve nurses' caring behavior in hospitals. This study used control group post-test-only design. The research was conducted in Medical wards of Private Hospital, Sukoharjo, Indonesia. Participants were 44 nurses divided into 2 groups, the control and the intervention group whose nurses received caring training using a protocol based on Jean Watson's caring carative factor. The tool used to collect data on nurses' caring behavior was the Caring Behavior Inventory-24 (CBI-24). Following the implementation of nurses demonstrating commendable caring behavior, as evidenced by the mean and standard deviation in the intervention group (119.18 ± 0.853) compared to the control group (87.50 ± 6.508). The results of showed a statistically significant difference between the nurse caring training intervention group and the control group with Asymp. Sig. (2-tailed) 0.000. Improving the character of caring behavior of nurses in various hospitals can be achieved through the implementation of training and mentoring based on the 10 carative factors approach with Jean Watson theory.